(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
The theory of foreign language teaching represents a systematic body of scientific views that explain how foreign languages are taught and acquired in educational settings. It integrates concepts from linguistics, pedagogy, psychology, and sociology to establish effective instructional principles. This article presents a paraphrased and plagiarism-resistant overview of the theoretical foundations of foreign language teaching, highlighting major approaches, learner-centered perspectives, and the evolving role of the teacher. The study emphasizes the necessity of aligning theory with classroom practice to ensure the development of communicative competence and meaningful language use.